Kolaborasi Mahasiswa KIP Pendidikan Agama Islam dengan Dosen dalam Meningkatkan Akreditasi dan Kualitas Program Studi - Dwi Putri; Syamsiah Depalina Siregar (PT. Willy Print Art, 2025)
This article explores the collaboration between KIP PAI scholarship students and lecturers at STAIN Mandailing Natal in improving study program accreditation and quality. Through a qualitative descriptive approach, this study highlights various forms of collaboration such as involvement in research, community service, and academic publishing. Data collection was conducted through observation, interviews, and documentation, analyzed by data reduction, classification, and verification. The findings show that structured collaboration contributes significantly to institutional performance indicators and academic competencies. Barriers include lack of communication space and time constraints. The study concludes that student-lecturer collaboration is a strategic asset for academic development.